2021
DOI: 10.2174/1871520621999210104181238
|View full text |Cite
|
Sign up to set email alerts
|

99mTechnetium- or Cy7-Labeled Fab(Tocilizumab) as Potential Multiple Myeloma Imaging Agents

Abstract: Background: Multiple myeloma (MM) is malignant hematologic disorder and the second most common blood cancer. Interleukin-6 (IL-6) has been identified as a crucial factor for proliferation and survival of MM cells and the overexpression of IL-6 receptor is being studied as a molecular target for therapeutic and diagnostic use in myelomas and other comorbidities. Tocilizumab is a humanized monoclonal antibody that binds IL-6R. Objective: We aim to label and evaluate Fab(Tocilizumab) with 99mTechnetium or Cy7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…And new therapeutic targets for HCC are urgently needed. IL‐6R is highly expressed in colorectal cancer, gastric cancer, multiple myeloma, prostate cancer and breast cancer, and it is closely associated with the development of these tumours 28–33 . IL‐6R promotes epithelial‐mesenchymal transition and stem transformation of tumour cells, and it promotes invasion and metastasis, thus enhancing the viability of tumour cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…And new therapeutic targets for HCC are urgently needed. IL‐6R is highly expressed in colorectal cancer, gastric cancer, multiple myeloma, prostate cancer and breast cancer, and it is closely associated with the development of these tumours 28–33 . IL‐6R promotes epithelial‐mesenchymal transition and stem transformation of tumour cells, and it promotes invasion and metastasis, thus enhancing the viability of tumour cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new therapeutic targets for HCC are urgently needed. It has been reported that IL-6R is highly expressed in colorectal cancer, gastric cancer, multiple myeloma, prostate cancer and breast cancer and is closely associated with the development of these tumors [18][19][20][21][22][23]. IL-6R can promote EMT and stem transformation of tumor cells, and promote invasion and metastasis, thus enhancing the viability of tumor cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new therapeutic targets for HCC are urgently needed. It has been reported that IL-6R is highly expressed in colorectal cancer, gastric cancer, multiple myeloma, prostate cancer and breast cancer and is closely associated with the development of these tumors [18][19][20][21][22][23]. IL-6R can promote EMT and stem transformation of tumor cells, and promote invasion and metastasis, thus enhancing the viability of tumor cells [24].…”
Section: Discussionmentioning
confidence: 99%